Pengaruh Supply Chain Management (SCM), Manajemen Kualitas dan Strategi Inovasi Terhadap Kinerja Operasional pada Perusahaan Manufaktur Di Kawasan Delta Silicon Cikarang - Candra Dwi Hardiana; Nanda Setiawan (Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine: (1) the influence of Supply Chain Management (SCM) on Operational Performance at manufacturing companies in the Delta Silicon Cikarang Industrial Area (2) the effect of Quality Management on Operational Performance at manufacturing companies in the Delta Silicon Cikarang Industrial Area ( 3) the influence of innovation strategies on operational performance in manufacturing companies in the Delta Silicon Cikarang Industrial Area (4) the influence of supply chain management (SCM), quality management and innovation strategies on operational performance in manufacturing companies in the Delta Silicon Cikarang area. This research is a quantitative descriptive study that aims to create a systematic, factual, and comprehensive picture of the facts and characteristics of a population or area. The population in this study were companies in the Delta Silicon Cikarang area. Sampling in this study using nonprobability sampling technique, namely saturated sampling method. Saturated sampling is sampling that is done using everything in the population. 74 questionnaires have been submitted to all companies aimed at company production managers in the Delta Silicon Cikarang area, with a return rate of 65 questionnaires. Based on the results of hypothesis testing using the SPSS V 26.0 t test device and simultaneously it shows that SCM has a significant positive effect on operational performance in manufacturing companies in the Delta Silicon Cikarang Industrial Area.